Ir. Afiffudin Desain Goal Alignment Perencanaan Mutu Pendidikan Islam - Afiffudin Afiff; Didin Hafidhuddin; Abas Mansur Taman (Lembaga Penelitian dan Pengabdian Universitas Nahdlatul Ulama Blitar, 2024)
Abstract The quality of Islamic education in school education units is currently a concern for the world of education in general, including in school education units with an Islamic spirit. Quality assurance of Islamic education requires a measurement matrix of both the output in the form of cognitive knowledge of Islamic values ​​and outcomes that include changes in student behavior in carrying out Islamic values ​​in everyday life. Stakeholders need collaborative efforts to encourage planning for the quality of Islamic education through Goal Alignment (GA). The purpose of the GA design is to create synergy and collaboration between stakeholders in order to realize the quality assurance of Islamic education. The GA method is a tracing design and tracking of all indicators of Islamic education quality achievement. In general, library research is used to explore GA designs in the perspective of Islamic worldview to be implemented in educational units, especially realizing the quality of education that has been determined. Vision-Mission-Value of the education unit is a collectively defined objectives of which each of stakeholders contribute to collectively implement and actively participate in evaluation. Both the results of the achievement of the vision-mission-value of the education unit and the role of stakeholders are evaluated to determine steps for continuous improvement towards the goals of the quality of education that have been set. In general, it can be concluded that the GA method is part of the Islamic worldview in almost all stages. The application of the GA method can be used to design quality assurance of Islamic education in school units and is a derivative of the Islamic worldview approach. Keywords : Goal Alignment, quality, islamic, education